Working Together : Improving Regulatory Cooperation and Information Exchange. (International Monetary Fund, 2007)
Globalization requires enhanced information flows among financial regulators. Standard-setting bodies for financial sector regulation provide extensive guidance, but financial sector assessments have often found that problems in cooperation and information exchange continue to constrain cross-border supervision and financial integrity oversight. In July 2004, the IMF organized a conference on cross-border cooperation for standard setters, financial intelligence units (FIUs), and financial regulatory agencies. This book brings together conference papers in which participants discuss: information exchange for an effective anti-money laundering/combating the financing of terrorism (AML/CFT) regime, in terms of both standards and practices; the standards for cooperation in the insurance sector; and the experiences of regulators from banking, securities, and unified regulatory agencies with international cooperation. The book also includes papers providing a general overview of international standards and their implementation and, on the basis of survey results, of practices among financial sector regulators and FIUs.